1968
DOI: 10.1136/bmj.1.5588.339
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into use of drugs preceding death from asthma.

Abstract: suggests that an upward trend in mortality may now be occurring (Gandevia, personal communication).We are grateful to the Registrar General of England and Wales for supplying many of the data, and for supplying them with minimal delay. We are grateful also to the Ministry of Health for information about the sale of aerosol bronchodilators; and to Miss A. Table I. In four instances no inquiries could be made as the name of the relevant general practitioner could not be ascertained. Two physicians did not respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
87
1
2

Year Published

1969
1969
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(91 citation statements)
references
References 4 publications
1
87
1
2
Order By: Relevance
“…The increase in deaths has been attributed to excessive use of aerosols containing sympathomimetic amines, principally isoprenaline (Speizer, Doll, Heaf & Strang, 1968). In the study of Speizer, Doll, Heaf & Strang (1968) 150 out of 174 patients had been using bronchodilators shortly before death.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in deaths has been attributed to excessive use of aerosols containing sympathomimetic amines, principally isoprenaline (Speizer, Doll, Heaf & Strang, 1968). In the study of Speizer, Doll, Heaf & Strang (1968) 150 out of 174 patients had been using bronchodilators shortly before death.…”
mentioning
confidence: 99%
“…The increase in deaths has been attributed to excessive use of aerosols containing sympathomimetic amines, principally isoprenaline (Speizer, Doll, Heaf & Strang, 1968). In the study of Speizer, Doll, Heaf & Strang (1968) 150 out of 174 patients had been using bronchodilators shortly before death. As isoprenaline administered by inhalation is absorbed rapidly into the blood stream and affects the heart (Chamberlain, 1967), it has been suggested that the deaths in these asthmatic patients may result from sympathomimetic-induced cardiac arrhythmias for example ventricular tachycardia or fibrillation (Speizer, Doll, Heaf & Strang, 1968).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially it was suggested 22 that it might result from sympathomimeticinduced cardiac arrhythmias, for example, ventricular tachycardia or fibrillation (Speizer et at, 1968). Subsequently one of the metabolites of isoprenaline was found to have 3-adrenoceptor blocking properties and it was thought that this might be harmful (Paterson, Conolly, Davies & Dollery, 1968) or that the heart might be sensitized to endogenous catecholamines by fluorinated hydrocarbons present in pressurized nebulizers (Taylor & Harris, 1970;Dollery, Draffan, Davies, Williams & Conolly, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…The observed increase in mortality from asthma between 1960 and 1966, particularly in the younger age groups, has been attributed to the excessive use of aerosols containing sympathomimetic amines, principally isoprenaline (Speizer, Doll, Heaf & Strang, 1968), and appears to have been geographically related to areas in which highly concentrated pressurized aerosols of isoprenaline were available (Stolley, 1972). Recognition of this possible relationship between isoprenaline inhalation and sudden death, and more disciplined use of this type of preparation has resulted in a reversal of the trend (Inman & Adelstein, 1969).…”
Section: Introductionmentioning
confidence: 99%